Analysis of Religious Court Judges' Decisions Class IA City Of Medan: Case Study Of Marriage Confirmation Case Reg Number: 51/Pdt.P/2015/PA Medan - Indra Bachri (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
This study starts from a decision of a judge of the Class IA Religious Court of Medan City who accepted and determined the application for Marriage Confirmation registered by Applicant I and Applicant II on behalf of Arifin bin Mhd Isya and Dahniar binti Burhanuddin who were married by the Judge Guardian on behalf of Anwar who in this case has the status of Assistant Marriage Registrar (P3N), then the decision issued by the judge of the Class IA Religious Court of Medan City on the application for Marriage Confirmation submitted by the applicant is legally flawed, because the judge did not take the PMA RI as a consideration, the judge only used the Circular Letter of the Supreme Court Number 3 of 2014 as a consideration where the Religious Court can validate the application for Marriage Confirmation submitted with the consideration of providing facilities to the applicant so that they can complete the population administration and civil registration which ultimately ignores the order of Law Number 1 of 1974 which mandates the Ministry of Religion to register marriages as well as to regulate marriage requirements where the position of the marriage guardian is a very urgent position in a marriage.